Tantangan Pengembangan Pendidikan Keguruan di Era Global - Oviyanti, Fitri (Nadwa, 2013)
Globalization barrage pass major changes to the world order as a whole. This era is characterized by the process of life worldwide, the advancement of science and technology, especially in the field of communication as well as the transfor-mation and cross-cultural. Changes brought about by globalization are also experienced by the world of education with teachers as practitioners. Challenges faced by teachers in the global era, such as the development of science and tech-nology are so rapid and fundamental; moral crisis that swept the nation and the state, social crisis and a crisis of identity as a nation. All that obviously requires prospective teachers and qualified professionals. Teacher education programs must be able to provide excellent service to the students so that they can esta-blish qualified teacher. Improving the quality of education will foster public confidence that still exist in the future?